Question
upstudy study bank question image url

37. Sabendo-se que \( \cos x=\frac{2 \sqrt{2}}{3} \), onde \( x \in\left[0 ; \frac{\pi}{2}\right]_{90} \), então \( \operatorname{tg} \frac{x}{2} \) é igual a: \( \begin{array}{lll}\text { a) } 3-2 \sqrt{2} & \text { b) } 3+2 \sqrt{2} & \text { c) } 2-\sqrt{2} \\ \text { d) } 3 \sqrt{2}-3 & \text { e) } 2 \sqrt{2}-3 & \end{array} \)

Ask by Watkins Adkins. in Brazil
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( \tan\left(\frac{x}{2}\right) = 3 - 2 \sqrt{2} \), choice a.

Solution

Para resolver o problema, vamos usar a relação entre o cosseno e a tangente do ângulo metade. A fórmula que relaciona a tangente do ângulo metade com o cosseno é: \[ \tan\left(\frac{x}{2}\right) = \frac{1 - \cos x}{\sin x} \] Sabemos que \( \cos x = \frac{2 \sqrt{2}}{3} \). Precisamos encontrar \( \sin x \) usando a identidade fundamental: \[ \sin^2 x + \cos^2 x = 1 \] Substituindo \( \cos x \): \[ \sin^2 x + \left(\frac{2 \sqrt{2}}{3}\right)^2 = 1 \] Calculando \( \left(\frac{2 \sqrt{2}}{3}\right)^2 \): \[ \left(\frac{2 \sqrt{2}}{3}\right)^2 = \frac{8}{9} \] Agora, substituindo na identidade: \[ \sin^2 x + \frac{8}{9} = 1 \] Isolando \( \sin^2 x \): \[ \sin^2 x = 1 - \frac{8}{9} = \frac{1}{9} \] Portanto, \( \sin x \) é: \[ \sin x = \sqrt{\frac{1}{9}} = \frac{1}{3} \] Agora que temos \( \sin x \) e \( \cos x \), podemos calcular \( \tan\left(\frac{x}{2}\right) \): \[ \tan\left(\frac{x}{2}\right) = \frac{1 - \cos x}{\sin x} = \frac{1 - \frac{2 \sqrt{2}}{3}}{\frac{1}{3}} \] Simplificando a expressão: \[ 1 - \frac{2 \sqrt{2}}{3} = \frac{3 - 2 \sqrt{2}}{3} \] Portanto: \[ \tan\left(\frac{x}{2}\right) = \frac{\frac{3 - 2 \sqrt{2}}{3}}{\frac{1}{3}} = 3 - 2 \sqrt{2} \] Assim, a resposta correta é: \[ \text{a) } 3 - 2 \sqrt{2} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

Para encontrar \( \operatorname{tg} \frac{x}{2} \), podemos utilizar a fórmula da tangente do ângulo pela metade: \[ \operatorname{tg} \frac{x}{2} = \frac{1 - \cos x}{\sin x} \] Sabendo que \( \sin^2 x + \cos^2 x = 1 \), podemos calcular \( \sin x \): \[ \cos x = \frac{2 \sqrt{2}}{3} \Rightarrow \sin^2 x = 1 - \left( \frac{2 \sqrt{2}}{3} \right)^2 = 1 - \frac{8}{9} = \frac{1}{9} \Rightarrow \sin x = \frac{1}{3} \] Substituindo os valores na fórmula, temos: \[ \operatorname{tg} \frac{x}{2} = \frac{1 - \frac{2 \sqrt{2}}{3}}{\frac{1}{3}} = \frac{3 - 2 \sqrt{2}}{1} = 3 - 2 \sqrt{2} \] Portanto, a resposta correta é a letra a) \( 3 - 2 \sqrt{2} \).

Related Questions

Latest Trigonometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy